Identification of common and specific cold resistance pathways from cold tolerant and non-cold tolerant mango varieties - Wang,Jian-hua; Feng,Xiaoyan; Ashraf,Muhammad Aleem; Li,Yufeng; Kong,Yu; Cai,Qiuliang; Xian,Shuli; Yin,Huixiang; Yu,Nai-tong (PeerJ, 2024)
Mango has frequently encountered severe climate and environmental challenges such as low temperatures, seriously affecting the sustainable development of the industry. In the study, physiological measurements showed that the activities of superoxide dismutase (SOD) and peroxidase (POD) were found to be higher in Jinhuang (JH) mango plants than those of Tainong (TN) mango plants under cold stress, indicating cold tolerant (JH) and non-cold tolerant (TN) mango varieties were firstly determined. Subsequently, transcriptomics showed 8,337 and 7,996 differentially expressed genes (DEGs) were respectively identified in JH and TN mango varieties treated at 4 °C for 36 h, while more DEGs (10,683 and 10,723) were screened when treated at 4 °C for 72 h. Quantitative real-time PCR (qRT-PCR) of the selected DEGs confirmed their transcriptional levels displayed agreement to the transcriptome data. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses showed two primary cold resistant regulation pathways, photosynthesis-antenna proteins pathway and photosynthesis pathway, were both significant annotated in the two mango varieties, indicating share the common regulation mechanism response to cold stress. However, five specific cold resistant pathways, such as amino acid and carbohydrate metabolisms, were identified in JH mango variety with cold stress for longer duration, indicating the specific regulation pathways in the cold tolerant mango varieties. Furthermore, 43 ethylene-responsive transcription factors (ERFs) were significantly annotated in JH mango after cold-treated for 72 h comparing with the control group, and three of them ERF109-1, ERF017-1 and ERF017-2 were highly expressed, which may play important regulatory roles in plant cold resistance. These results provided insights into the primary and specific molecular mechanisms of different mango varieties resistance to chill.
Keywords: Mango; Abiotic stress; Cold resistance; Omics; Ethylene-responsive transcription factor